Case Report: Analysis of Plasma Extracellular Vesicles in a Triple Negative Spindle-Cell Metaplastic Breast Cancer Patient - Vannini, Ivan; Urbini, Milena; Melloni, Mattia; Rossi, Tania; Gallerani, Giulia; Palleschi, Michela; Azzali, Irene; Puccetti, Maurizio; Martinelli, Giovanni; Fabbri, Francesco (Frontiers in Medicine, 2022)
Metaplastic breast cancer (MpBC) is a rare tumor representing 1% of all breast malignancies. The prognosis of this histologic subtype is actually poor and there are no current clear-cut therapeutic guidelines. Hence, despite its uniqueness, its aggressive prognostic profile strongly encourages further studies to identify new markers and therapeutic targets. Herein, we report a case of 32-years-old patient affected with of triple negative spindle-shaped MpBC. The research of molecular targets on the primary tumor did not allow performing an effective therapeutic choice. Extracellular Vesicles (EVs) are under intense study as new potential pathophysiological markers and targets for therapeutic applications, in different tumors for their role in tumor onset, progression and aggressiveness. Here, we examined the involvement of EVs in this case, to look into the MpBC microenvironment willing to identify new potential molecular targets, pathways of aggressiveness, and markers of prognosis and therapeutic efficacy. Firstly, we characterized MpBC patient EV dimensions and surface proteins. Moreover, we analyzed the EV RNA cargo supposed to be delivered to nearby and distant recipient cells. Interestingly, we observed a dysregulation EV-contained miRNAs, which could determine an increased expression of oncogenes in the tumor microenvironment, probably enabling cancer progression. These data suggest that the characterization of miRNA cargo of EVs could be important for the identification of new markers and for the application of future new target therapies.